Correcting double outward box distributed residuals by WCEV - Celik, Resit (TAYLOR & FRANCIS INC, 2017)
Double outward box distributed residuals are another type of non monotonic heteroscedasticity that severely violates homoscedasticity assumption. In this study Celik's (2015) WCEV is applied to double outward box distributed residuals to provide homoscedasticity for simple and multiple regression models.
Keywords: Centered external variable; Double outward box distributed residuals; Non monotonic type of heteroscedasticity; Weighting by the absolute centered external variable; REGRESSION-MODELS; HETEROSCEDASTICITY; Mathematics